Low-power picosecond resonance Raman evidence for histidine ligation to heme a3 after photodissociation of CO from cytochrome c oxidase - Schelvis, Johannes; Deinum, Geurt; Varotsis, Constantinos (My University, 1997)
Several models have been proposed for the ligand dynamics in the heme a32+/Cu(B)1+ binuclear pocket in cytochrome oxidase following CO photodissociation. These range from straightforward heme pocket relaxation to a variety of ligand exchange processes that have been proposed to be of relevance to the proton pumping function of the enzyme. To provide discrimination between these models, we have used picosecond time-resolved, pump-probe resonance Raman spectroscopy to study the photolysis process in the enzyme isolated from beef heart and from Rhodobacter sphaeroides. The intermediate observed within 5 ps of photolysis with low-energy probe pulses (10-20 nJ/pulse) is the high-spin, five-coordinate heme a32+ to which a histidine is ligated, as indicated by the observation of the Fe-His vibration at 220 cm-1. Several control experiments demonstrate that the probe pulse energy is sufficiently low to avoid promoting any significant photochemistry during the spectral acquisition phase of the pump-probe experiment. From these observations, we conclude that histidine is ligated to high-spin heme a32+ on the picosecond time scale following photolysis. Since H376 is the proximal a32+ ligand in the CO complex, our results indicate that this proximal ligation survives photolysis and that the control of the access of exogenous ligands to the heme a3 site by means of a ligand exchange process can be ruled out. We observe similar picosecond transient resonance Raman spectra for the CO complex of Rb. sphaeroides cytochrome c oxidase. From these results and earlier time-resolved Raman and FTIR measurements, we propose a model for the relaxation dynamics of the heme as pocket that involves picosecond migration of CO to the Cu(B) center and relaxation of the a32+-proximal histidine bond on the microsecond time scale following CO photolysis
Keywords: Fourier transform infrared spectroscopy; Cytochrome oxidase; Ligand binding (Biochemistry); Molecular dynamics; Photochemistry; Raman spectrometry; Enzymes; Heme